Tinjauan Kriminologis Terhadap Tindak Pidana Perjudian Sabung Ayam Dalam Masyarakat Di Wilayah Hukum Kabupaten Magetan - Mutia, Meiana Wahyu Retno (2017)
This study aims to determine the factors that cause the actors do the Crime of Gambling cockfighting in the community and to know the efforts the Police in combating crime cockfighting gambling going on in society. This study uses criminological-sociological approach. Data collection techniques in this research is the study of literature and field study. The results showed that (1) Factors that lead offenders to commit gambling cockfight is a factor of the weak implementation of the religion, the environment, customs, economy, weak law enforcement, factors intentions and opportunities, (2) Efforts to police in the prevention of gambling cockfighting is through action preventive, persuasive action and repressive measures.